2015
DOI: 10.1016/j.jvoice.2014.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of Intensive Voice Therapy for Vocal Fold Nodules Via Telepractice: A Pilot Feasibility and Efficacy Study

Abstract: Analyses were performed by a speech-language pathologist and an otolaryngologist independent to and blinded to the study. Participants also completed the Voice Handicap Index and a telepractice satisfaction questionnaire, or an anticipated satisfaction questionnaire, before and after treatment.Results. Significant improvements were found in perceptual, vocal fold function, acoustic and physiological parameters as well nodule sizes and patient perceptions of voice-related quality of life post treatment. Partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0
25

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(93 citation statements)
references
References 38 publications
1
67
0
25
Order By: Relevance
“…As this research on FK technique in vocal therapy is unprecedented, there were not found, to the date, similar findings to compare the results. However, the positive results found in the acoustic analysis are according to two studies that performed a form of LSVT in subjects with vocal fold nodules and showed significant reduction of jitter and shimmer and increased f0 (21,23) , as well as reducing the NHR (23) . The first study was conducted with 53 women and their goal was to compare the LSVT (eight sessions in three weeks) to traditional therapy (eight sessions in eight weeks).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As this research on FK technique in vocal therapy is unprecedented, there were not found, to the date, similar findings to compare the results. However, the positive results found in the acoustic analysis are according to two studies that performed a form of LSVT in subjects with vocal fold nodules and showed significant reduction of jitter and shimmer and increased f0 (21,23) , as well as reducing the NHR (23) . The first study was conducted with 53 women and their goal was to compare the LSVT (eight sessions in three weeks) to traditional therapy (eight sessions in eight weeks).…”
Section: Discussionmentioning
confidence: 99%
“…To be included, the subjects should: be a teacher of kindergarten, elementary, middle or top of public or private networks of a medium-sized city of state of inner; being female (3,4,24) ; be in the age group between nineteen and sixty years old (4,11,23) ; has any of the following laryngeal conditions diagnosed by medical ENT: Normal larynx; posterior glottal opening or medio-posterior glottal opening, anterior gaps (caused by secondary muscle fatigue hypertension), supraglottic hyperconstriction (all of these are classified as "non-structural laryngeal disease") vocal fold nodules, vocal fold polyps, cysts, vasculodysgenesis or even leukoplakia, edema, laryngitis, thickening, irregularities edges of the vocal folds, hyperemia (all those classified as "structural laryngeal disease"); present habits and/or suggestive vocal behavior of hyperfunction (7,10) , and hours worked per week at or above to 20 hours.…”
Section: Participantsmentioning
confidence: 99%
See 3 more Smart Citations